Exhibition of Mason-Marks copied from Melrose Abbey, Dryburgh, Jedburgh, &c - Smith, John Alex (Proceedings of the Society of Antiquaries of Scotland, 1863)
The author describes how mason’s marks are used in building materials to note which mason constructed each part of the structure. He suggests that if a researcher had a record of mason’s marks that were used across Scotland in different time periods, it might be possible to cross-reference them and discover if the same masons worked on buildings with similar styles, or to check whether part of a building was a later addition based on when the mason’s marks are from. Meeting notes for 9 June, 1862 are appended.